Total synthesis guided structural revision of peribysin family natural products and development of novel method for enone transposition - Athawale, P. (CSIR-National Chemical Laboratory, Pune, 2021)
The work included in this thesis is mainly based on the total synthsis of the natural products and development of useful synthetic methods. Herein we have developed a unified strategy to access the peribysin family natural products which possess potent cell adhesion inhibitory activities. The structures of the peribysins A, B, C, F, and G were revised based on NMR, optical rotation and single crystal X-ray data. With this exercise we were able to conclude that the peribysins isolated from marine animal source needs stereochemical revision and those isolated from terrestrial plant source does not need any revision. During the synthesis of peribysins we sought to develop a method for enone transposition which was achieved with help of silyl masking group. The highlights of the method includes Z-selectivity, enantio-switching and functional group shuffling in selected examples. The method was successfully tested with more than 14 substrates and applied for the total synthesis along with structural revision of peribysin D. Additionally, formal synthesis of E-guggulsterone and E- volkendousin was achieved. Lastly, an unexpected but useful transformation of dienones to diene-diones discovered during a double bond migration reaction using DBU in acetonitrile. Further, method was tested with 14 substrates and applied for the synthesis of (±)-pleodendione with improved yields.
Keywords: Total Synthesis; Structural Revision; Peribysin; Enone Transposition